AN INCREASING KNOWLEDGE ABOUT THE IMPORTANCE OF OCCUPATIONAL SAFETY AND HEALTH (K3) IN HOUSEKEEPING LABOR HOTELS - Budhi Santri Kusuma; Abdurrozzaq Hasibuan; Suhela Putri Nasution; Arvina Putri Utami; Azila Rahimah Dalimunthe (INFOKUM, 2022)
Occupational Safety and Health (K3) is defined as science and its application technically and technologically to prevent work accidents and occupational diseases from occurring in any work performed. From a legal perspective, OSH can be defined as an effort to protect every workforce and other people who enter the workplace are always in a healthy and safe condition and the resources of the production process can be carried out safely, efficiently and productively. The main objective in implementing K3 based on Law no. 1 of 1970 concerning Occupational Safety, namely protecting and guaranteeing the safety of every worker and other people in the workplace, guaranteeing that every source of production can be used safely and efficiently, and increasing national welfare and productivity. The method used in this article is a qualitative method, namely data that is narrative in nature, not numbers, where this data source comes from various journal references to strengthen reading results. therefore the hotel implements the K3 System in order to maintain the safety and health of the workforce and maintain the quality of the hotel. The method used in this article is a qualitative method, namely data that is narrative in nature, not numbers, where this data source comes from various journal references to strengthen reading results. therefore the hotel implements the K3 System in order to maintain the safety and health of the workforce and maintain the quality of the hotel. The method used in this article is a qualitative method, namely data that is narrative in nature, not numbers, where this data source comes from various journal references to strengthen reading results.